THE LONG AND WINDING ROAD: CONFRONTING SEXUAL VIOLENCE ON WOMEN IN PESANTREN - Wardana, Khansadhia Afifah; Rahayu, Rahayu; Sukirno, Sukirno (Masalah-Masalah Hukum, 2023)
One of the most prominent educational institutions that shaped the societal development of Indonesia as of today, would be Pesantren, the Islamic boarding school that spread nationwide. The existence of pesantren has managed to help open more doors in advancing women’s education, but such achievement came with many challenges that put other women’s rights in jeopardy. Discrimination, sexual violence, and the imbalance of power relations cause mayhem to women’s rights, not only in terms of education but also for their religious freedom. This paper provides a qualitative study on the challenges that women faced in Pesantren conducted through observation and study of cases. A gender perspective is needed in order to ensure the protection of women in Pesantren.